The crisis of imprisonment: Protest, politics, and the making of the American penal state, 1776-1941 - McLennan, Rebecca M (Cambridge University, 2013)
In the Age of Jackson, private enterprise set up shop in the American penal system. Working hand in glove with state government, by 1900 contractors in both the North and the South would go on to put more than half a million imprisoned men, women, and youth to hard, sweated toil for private gain. Held captive, stripped of their rights, and subjected to lash and paddle, these convict laborers churned out vast quantities of goods and revenue, in some years generating the equivalent of more than $30 billion worth of work. By the 1880s, however, a growing cross-section of American society came to regard the prison labor system as morally corrupt and unbefitting of a free republic: it fostered torture and other abuses, degraded free citizen-workers, corrupted the government and the legal system, and defeated the supposedly moral purpose of punishment. The Crisis of Imprisonment tells the remarkable story of this controversial system of penal servitude - how it came into being, how it worked, how the popular campaigns for its abolition were ultimately victorious, and how it shaped and continues to haunt America's modern penal system.